Food security intervention mechanisms in the drought-prone rural areas of Tigray - Gebre, Tewelde; Abraha, Zenebe; Zenebe, Amanuel; Zeweld, Woldegebrial (Frontiers in Nutrition, 2024)
Tigray is one of the food-insecure regions with many people living under chronic hunger. Proper intervention mechanisms are vital for addressing food insecurity. Yet, food security intervention mechanisms of various levels are not researched well. Besides, previous studies have rarely addressed the objectives of food security intervention mechanisms in relation to the four pillars of food security: availability, access, utilization and stability. Thus, this study aims to investigate the food security intervention mechanisms in the drought-prone rural areas of Tigray in relation with the major components of food security. This study has employed a crosssectional study design based on a mixed research approach with primary and secondary data. For this, 363 households from three selected drought-prone rural districts, i.e. Atsbi-wenberta, Irob and Hintalo-wejerat were studied. Primary data were collected using questionnaires and key-informant interviews. And, secondary data were collected from relevant archives and policy documents. The obtained data were analyzed descriptively and content-wise. Findings show that there were several international interventions intended to halt food insecurity sustainably through financial aid, but many of the interventions were found to be responding to humanitarian crises mainly the food shortages. Ethiopia's Food and Nutrition Policy, Food Security Program, Food Security Strategy, and Food Security Pack program were the food security intervention mechanisms at the national level. These interventions were found to be inconsistent with each other in their intended goals. Regionally, no food security strategy or program was found intervening to the prevailing food insecurity of Tigray. More notably, the region has no food security bureau or office that deals with food security issues of the region. At a community level, food aid and PSNP transfers have been the usual food security intervention mechanisms. 35.6 percent (77,010) of the population in the study rural districts were found to be rural PSNP beneficiaries. The food aid and PSNP transfers were outrageously insufficient for the recipients to cope with food insecurity. Therefore, intervention mechanisms should focus on enhancing vulnerable households' coping and adaptive capacities and all the food security intervention mechanisms of various levels should be integrated into the common goal of achieving food security.